2004
DOI: 10.1183/09031936.04.00079704
|View full text |Cite
|
Sign up to set email alerts
|

Chronic thromboembolic pulmonary hypertension

Abstract: Pulmonary arterial hypertension is a severe disease that has been ignored for a long time. However, over the past 20 yrs chest physicians, cardiologists and thoracic surgeons have shown increasing interest in this disease because of the development of new therapies, that have improved both the outcome and quality of life of patients, including pulmonary transplantation and prostacyclin therapy.Chronic thromboembolic pulmonary arterial hypertension (CTEPH) can be cured surgically through a complex surgical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
353
0
44

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(408 citation statements)
references
References 33 publications
11
353
0
44
Order By: Relevance
“…Previously, large patient series have been derived from medical [15][16][17] and surgical databases [18,19], with the most recent representing Data are presented as n or n (%). CTEPH: chronic thromboemolic pulmonary hypertension; PEA: pulmonary endarterectomy; PAH: pulmonary arterial hypertension; CVD:…”
Section: Discussionmentioning
confidence: 99%
“…Previously, large patient series have been derived from medical [15][16][17] and surgical databases [18,19], with the most recent representing Data are presented as n or n (%). CTEPH: chronic thromboemolic pulmonary hypertension; PEA: pulmonary endarterectomy; PAH: pulmonary arterial hypertension; CVD:…”
Section: Discussionmentioning
confidence: 99%
“…Often, it is permanently curative, as long as patients remain on lifelong anticoagulation, and may result in a substantial improvement in cardiopulmonary hemodynamics [8,12,[26][27][28]. Significant improvements in New York Heart Association functional class, dyspnea scores, gas exchange/exercise capacity, and long-term survival have been reported [25•, 29-31].…”
Section: Surgerymentioning
confidence: 99%
“…However, medical therapies directed at treating PH have been investigated and increasingly used in subcategories of CTEPH patients [9,10]: 1) patients deemed inoperable because of extensive distal precapillary vasculopathy not amenable to surgery or those who have significant comorbidities that contraindicate surgery [11]; 2) the 10% to 15% of patients who have residual PH following thromboendarterectomy surgery [12]; and 3) patients with severe hemodynamic compromise, as a bridge to surgery. Xa inhibitors (fondaparinux) may be considered.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the incidence of CTEPH is usually estimated to be <1% among patients with acute PE, [2][3][4] several studies have proposed that this low incidence was an underestimation and showed approximately 4%, a relatively high incidence of CTEPH after PE. [5][6][7] In addition, it has not been shown why some PE patients develop CTEPH and others do not.…”
Section: Introductionmentioning
confidence: 99%